Management of Unilateral Vocal Fold Paralysis after Thyroid Surgery with Injection Laryngoplasty: State of Art Review - Liao, Li-Jen; Wang, Chi-Te (Frontiers in Surgery, 2022)
Background Unilateral vocal fold paralysis (UVFP) after thyroid surgery often leads to significant morbidity including dysphonia, dysphagia, and aspiration. Injection laryngoplasty (IL) is an effective treatment of UVFP with numerous readily available materials. However, few studies focus on IL for UVFP following thyroidectomy. Objectives This review aims to critically review current literature to determine the timing, materials, methods and outcomes of IL for UVFP after thyroid surgery. Type of Review Literature review. Methods A literature review was performed using the Pubmed, Medline and EMBASE databases. All relevant articles published in English addressing the effect of IL in post thyroid surgery related UVFP were analyzed. Studies using IL for UVFP of multiple etiologies were excluded. Meta-analysis was conducted using fixed and random effect model. Results Five original studies were identified, including 214 patients received IL for UVFP following thyroid surgery. Two studies injected autologous fat via direct suspension laryngoscope under general anesthesia, while the other 3 studies injected polyacrylamide, hyaluronic acid, and polymethyl methacrylate from cricothyroid membrane under local anesthesia. All 5 studies reported improved voice outcomes of IL for post-thyroidectomy UVFP. Meta-analysis showed MPT increased for 3.18 s (95% CI: 2.40–3.96, fix effect model) after IL. Another common acoustic parameter, jitter (%) also improved for 1.46 (95% CI: 0.73–2.19, random effects model) after IL for post-thyroidectomy UVFP. Conclusions This review supported that IL can improve the voice outcome for post-thyroidectomy UVFP. Autologous fat remains a good augmentation material with a potential longer lasting effect. More research and long-term surveys are needed to document the safety and longevity of other synthetic materials.